2017
DOI: 10.1002/adhm.201700207
|View full text |Cite
|
Sign up to set email alerts
|

A Freeze‐Concentration and Polyampholyte‐Modified Liposome‐Based Antigen‐Delivery System for Effective Immunotherapy

Abstract: Immunotherapy is an exciting new approach to cancer treatment. The development of a novel freeze-concentration method is described that could be applicable in immunotherapy. The method involves freezing cells in the presence of pH-sensitive, polyampholyte-modified liposomes with encapsulated ovalbumin (OVA) as the antigen. In RAW 264.7 cells, compared to unfrozen, freeze-concentration of polyampholyte-modified liposomes encapsulating OVA resulted in efficient OVA uptake and also allowed its delivery to the cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…More advanced strategies to facilitate immunogenic delivery into the cytosol depend on the lower pH of the early/late endosome . For example, CaP skeleton as a shell protects CpG oligonucleotides from clearance by macropinocytosis and responds to acidic organelle environment for on‐command release in cytosol .…”
Section: Nanomaterials For Target Deliverymentioning
confidence: 99%
“…More advanced strategies to facilitate immunogenic delivery into the cytosol depend on the lower pH of the early/late endosome . For example, CaP skeleton as a shell protects CpG oligonucleotides from clearance by macropinocytosis and responds to acidic organelle environment for on‐command release in cytosol .…”
Section: Nanomaterials For Target Deliverymentioning
confidence: 99%
“…This is because the adsorption and internalization of proteins into the cells generally have a linear relationship, as the number of particles that adhere to the cell membrane will reflect that of particles being transferred inside the cells, as has been observed in our previous studies. 7,8,52,53 Overall, this detailed study demonstrated the efficient use of the ice-crystal-based freezing approach to the internalization of proteins with the help of a unique polyampholyte cryoprotectant.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The release of OVA from MRPRPNs and PRPNs was determined by analyzing the florescence intensity of pyramine as reported in previous studies [34,[47][48][49]. Briefly, pyramine (50 mL)-loaded MRPRPNs were dispersed in different pH buffers, i.e.…”
Section: Ova Content Determination (% Ee)mentioning
confidence: 99%